Penerapan Arsitektur Neo-Vernakular Pada Tempat Istirahat dan Pelayanan Jalur Lintas Selatan Kabupaten Pacitan (Program Studi Arsitektur Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2023)
Road construction for the southern route is a road network to connect several cities in the Java Island. This southern route have the possibility of an accident. Generally, accidents occur due to unroadworthy’s vehicles and the tired drivers. Therefore, in order to reduce the rate of accidents on the southern route, the government is required to provide rest areas for road users. Rest Area is a place and facilities provided for road users so that both drivers, passengers and their vehicles can rest temporarily. Unfortunately, there is no Rest Area along the southern route of Pacitan Regency. Meanwhile, the distance from one city to another is quite far, so a Rest Area is needed so that road users and their vehicles can rest for a while. The planning for this rest area is using Neo-Vernacular Architecture theme, to raise the local traditional characteristics of the Pacitan district, which are adapted to modern developments. That way it will create a uniqueness in the building that can attract visitors from various walks of life.